Pengaruh Penggunaan Media Pembelajaran Quizizz Terhadap Minat Belajar Peserta Didik Kelas VII MTsN 1 Kota Makassar - Yuliany, Nur; Rahmawati Nur; Besse Alfiani; Riska Yunus; Nurhalifah; Magfira Syahrul; Saskia Hairunnisa; Sri Ayu Amaliyah Ramadhani; Rahmatullaili (Faculty of Tarbiyah and Teacher Training, 2024)
The aim of this service activity or PLP 2 is to help students inscrease their interest or motivation in learning mathematics. The implementation method used in this activity is identifying the learning objectives to be achieved, using quizizz learning media to increase student’s interest in learning in mathematics subjects. Based on the learning activities that have been carried out through the use of quizizz learning media, it is able to increase student’s interest ini learning because it provides a new atmosphere, making it easier fot students to understand the learning material. Quizizz has several features that don’t make students bored and fed up with learning, including: there is a countdown time when working on questions, there are memes with characters when students are not correct in doing questions, there are random awards when students answer questions correctly.